Media Image of Mothers and Motherhood on the Online Parenting Website mama:Du - Trysińska, Magdalena (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The media play a significant role in promoting a new model of motherhood, observed in social life in Poland. The aim of this article is to reconstruct the media’s portrayal of motherhood and maternity. The research material comprises titles and leads of press articles published on the online website mama:Du. The methodological foundation is drawn from the premises of cultural linguistics and the processes of concept profiling. The research material distinguishes profiles such as a suffering and exhausted mother, a single mother, an independent mother, a (non)working mother, and a mother as a woman. Analysis indicates that despite changes in the social perception of a woman’s role, the website presents a unidimensional image of motherhood, reducing women to the mother-child dyad. This image aligns with the stereotype of the mother as a caregiver. However, there are sparse signals of overturning these prevalent stereotypes in texts showcasing mothers who call for alteration of established norms. Nevertheless, the feminine aspect of a mother, as a woman who takes care of herself and has her own interests beyond caregiving duties, remains invisible. Thus, the medium reflects a realistic, consistent with Polish realities portrayal of motherhood and maternity, gradual striving towards its transformation.